THE IMPLEMENTATION OF FAST METHOD FOR ACREDITATION FORM SUPPORTING DATA - Dewi Kania Widyawati; Zuriati Zuriati (Proceeding International Conference on Information Technology and Business, 2016)
The implementation phase at FAST method is established after the Construction Phase is already completed with a reference used in implementing the application based on use case, class diagram andactivity diagram fully designed at the previous phase.The testing conducted useswhite box testing. Of the advantages is when the application is tested, it can find out codes and strategies that take a role in developing the functions of each application module effectively. This seems to support the information system development with FAST method which one of its benefits to give a performance and accurate information. At this phase there are several things to test, namely: unit testing, static and dynamic analysis, scope of statement and mutation test. The case study used in implementing the application is the form supporting data at Lampung State Polytechnic.Keyword: class diagram , Construction Phase, FAST, use case, activity diagram, white box testing.